Reframing Genesis 3:16: Eve’s Creation Memoir - Frey, Mathilde (Religions, 2024)
I will read Genesis 3:16 through the lens of Genesis 4. While Eve has become a fixed object in traditional interpretation as a dangerous temptress for man and the cause of humanity’s fall into sin, her story does not end in this chapter. Eve’s creative agency as “mother of all living” becomes the framework for the drama that unfolds in Genesis 4. Her body and her voice carry the story of life into the future. This essay shows the connection between Genesis 3:16 and the story in Genesis 4 by moving beyond a linguistic analysis of the common verbs, mashal and teshuqah. I will read the two texts together with the ancient scribes who distinguished Genesis 3:16 by placing this one verse between two setumah markers. Likewise, the story of Eve in Genesis 4:1–5:2 is placed between two setumah markers, thereby showing that ancient Hebrew readings emphasized a close relationship between Genesis 3:16 and Genesis 4:1–5:2. This is opposed to the Christian chapter division, which separates Genesis 3 from the story in Genesis 4, and places Genesis 3 in an authoritative position for the sake of extrapolating the doctrine of the fall into sin with the woman playing the central role in the fall story. I will further engage in deep reading, literary analysis, and performance criticism, and argue that Eve tells her own creation story with masterful subversiveness and creative audacity. The attempt of the essay is to reorient the dominant negative view of Eve toward a more positive, complex, and nuanced reading of her character in the Genesis text.